The Relationship Of Online Game Addiction To Changes In Emotional Regulation Of Medical Faculty Students At Maranatha Christian University - Ivone, July; Sinaga, Irvan Amanda; Hasianna, Stella Tinia (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2025)
Online games are a type of game that can be played on various devices and connected to the Internet network so that it can be used to play online games, if played continuously with a long intensity can cause a person to be addicted to online games and have an impact on mind disorders and emotional and mental health. Faculty of Medicine students have a busy schedule, so they play online games to overcome the boredom. This study is to determine the relationship between online game addiction and changes in emotional regulation of Maranatha Christian University Medical students. This study used an analytical method with a cross sectional research design with a total research sample of 132 students. The results of the spearman correlation test where the p value = 0.001 is obtained, meaning that there is a very significant correlation between online game addiction and emotional regulation. The r value is 0.688, which means that there is a strong relationship between online game addiction and emotional regulation and has a positive pattern. There is a strong relationship between online game addiction and emotional regulation in Maranatha Christian University Medical faculty students class of 2021 and 2022.